TINJAUAN KELENGKAPAN FORMULIR RESUME MEDIS BERDASARKAN ELEMEN PENILAIAN MIRM 15 STANDAR NASIONAL AKREDITASI RUMAH SAKIT (SNARS) DI RSU IMELDA PEKERJA INDONESIA - Jihan Alna; Jhon Barker Liem (Jurnal Kesehatan Sejahtera, 2024)
Incompleteness in filling out medical resumes will greatly affect the assessment of Hospital accreditation. This study aims to determine the completeness of filling out medical resume forms based on the MIRM 15 SNARS Edition 1.1 assessment elements at RSU Imelda Buruh Indonesia Medan. This study uses quantitative and qualitative methods, with a population of all medical resume forms at RSU Imelda Buruh Indonesia Medan. A sample of 93 medical resumes was rounded up to 100 medical resume forms. Based on the results of the study, it was found that the completeness of the medical resume forms was 76 medical resume forms (70%) and 30 medical resume forms (30%) were incomplete. Based on the SNARS Edition 1.1 assessment score, the number of complete medical resume forms was 76% with a score of 5 (partially fulfilled) because the achievement range was 29% -79%. The highest completeness of the medical resume form at RSU Imelda Buruh Indonesia is found in the components of patient history, diagnostic examination, diagnosis, therapy procedures and actions, drugs given and drugs when the patient is discharged from the hospital, patient health condition (current status) and follow-up instructions as much as (100%) medical resume forms and the lowest completeness is found in physical examination (15%) indications for patient hospitalization (6%), comorbidities (12) and patient/family signatures as much as (24%) medical resume forms. The researcher's suggestion is that continuous socialization should be held to increase knowledge for medical personnel about filling out the completeness of the medical resume form according to SNARS at RSU Imelda Buruh Indonesia Medan